An Observation on Implementation of Classroom Assessment in Technical and Vocational Education and Training (TVET) Subject Area - Hashim, Suhaizal; Zakariah, Siti Hajar; Taufek, Fatin Afiqah; Zulkifli, Nurul Nadwa; Che Lah, Noor Hidayah; Murniati, Dewi Eka (Journal of Technical Education and Training, 2021)
Classroom assessment is continuously assessment throughout the teaching and learning process and used in totally in every subjects. Assessment is designed to provide the understanding and help school administrators and teachers in performing assessment process in order to obtain the feedback on students learning development and pedagogical effectiveness. However, there been an issue of assessment that faced by teachers which is the lack of training and skills in techniques that effect the level of confidence in implementation of school based assessment. Therefore, this study aims to identify the problems faced by teachers in implementing classroom assessment for one of the Technical and Vocational Education and Training (TVET) subject area which is Design and Technology. Respondents comprised of 26 teachers were randomly selected from 15 secondary schools in Johor. Descriptive studies of qualitative research were selected to get an idea on experiences and the data would be segmented according to the coding scheme using thematic analysis methods. The results showed that the major problem in management of classroom assessment processes faced by teachers were on insufficient resources. Besides, the analysis results also shows that other main difficulties in conducting the classroom evaluation process is on student performance and in the process of classroom assessment were on time management. Whereas, the resources used by teachers to help students in the classroom assessment process emphasizing on the use of digital resources. Thus, it can be concluded that the classroom assessment process implemented by the teacher has not yet achieved the goals set by the Ministry of Education (MOE) and teachers need more resources to implement classroom assessment process in order to achieve the outcome of the learning.